2018
DOI: 10.1002/lary.27626
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngology Residency Interviewing Dates and Practices: What Should an Applicant Expect?

Abstract: Objectives/Hypothesis Scheduling otolaryngology interviews may be a challenge for residency applicants due to overlapping interview dates. Our objective was to identify otolaryngology interview date patterns and scheduling conflicts over the past six application cycles. Study Design Retrospective review of otolaryngology online forums (http://Otomatch.com and Student Doctor Network). Methods Online threads related to residency interview dates posted during the 2012 to 2013 through 2017 to 2018 interview season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Similarly, otolaryngology instituted a 3-week interview invitation window, limiting the period during which applicants must remain vigilant. 13 In obstetrics and gynecology, over 90% of applicants reported these reforms reduced anxiety in the application process, with the 72-hour response period representing the most important change. 14 Additional benefits include fewer distractions for students participating in clinical rotations during this period, reduction in hoarding, and fewer late cancellations as applicants receive invitations from more desirable programs.…”
Section: Universal Interview Invitation Releasesmentioning
confidence: 99%
“…Similarly, otolaryngology instituted a 3-week interview invitation window, limiting the period during which applicants must remain vigilant. 13 In obstetrics and gynecology, over 90% of applicants reported these reforms reduced anxiety in the application process, with the 72-hour response period representing the most important change. 14 Additional benefits include fewer distractions for students participating in clinical rotations during this period, reduction in hoarding, and fewer late cancellations as applicants receive invitations from more desirable programs.…”
Section: Universal Interview Invitation Releasesmentioning
confidence: 99%
“…This forces applicants who receive the largest number of interviews to decide between programs, which opens up interviews for other applicants. An analysis of the 2012 to 2018 Match years showed that although the 2017 Match contained the least overlap between interview dates, this time period coincided with 10 programs entering the Supplemental Offer and Acceptance Program (SOAP) and 14 unfilled spots 31 , 32 . By minimizing interview date overlap, programs enabled interview hoarding by certain applicants, which may negatively affect “less qualified” applicants.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the 2012 to 2018 Match years showed that although the 2017 Match contained the least overlap between interview dates, this time period coincided with 10 programs entering the Supplemental Offer and Acceptance Program (SOAP) and 14 unfilled spots. 31,32 By minimizing interview date overlap, programs enabled interview hoarding by certain applicants, which may negatively affect ''less qualified'' applicants. This phenomenon contradicts the traditional notion that programs should attempt to minimize overlapping interview dates.…”
Section: Signaling Systemmentioning
confidence: 99%
“…The timing of the single interview offer date is selected to balance the need for programs to meaningfully review applications with the scheduling logistics of applicants to complete interviews within the historical window for most otolaryngology programs. Programs have access to complete applications, including the medical student performance evaluations, on September 29, 2021, and most otolaryngology programs conduct interviews in the months of December or January 9 . Hopefully, over a full month of application review will encourage holistic review of applications and deter programs from quickly sifting through applications via cutoff scores or screening metrics.…”
Section: Figurementioning
confidence: 99%